2021
DOI: 10.3390/ijms22126191
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Graft-versus-Host Disease in a Chemotherapy-Based Minor-Mismatch Mouse Model Features Corneal (Lymph-) Angiogenesis

Abstract: Ocular graft-versus-host disease (oGVHD) is a fast progressing, autoimmunological disease following hematopoietic stem cell transplantation, leading to severe inflammation of the eye and destruction of the lacrimal functional unit with consecutive sight-threatening consequences. The therapeutic “window of opportunity” is narrow, and current treatment options are limited and often insufficient. To achieve new insights into the pathogenesis and to develop new therapeutic approaches, clinically relevant models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Lymph nodes of all mice in each of the 3 groups (vehicle, HT, and OPT3-treated) were removed from all animals on the last day and mashed the same day through a cell strainer, as previously described [ 55 ]. Briefly, single-cell suspensions were transferred to FACS buffer (0.5% N,O-bis (trimethylsilyl)acetamide—BSA, 1% FBS, and Ethylenediaminetetraacetic acid—EDTA 1:50 in DPBS—Thermo Fisher Scientific, Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph nodes of all mice in each of the 3 groups (vehicle, HT, and OPT3-treated) were removed from all animals on the last day and mashed the same day through a cell strainer, as previously described [ 55 ]. Briefly, single-cell suspensions were transferred to FACS buffer (0.5% N,O-bis (trimethylsilyl)acetamide—BSA, 1% FBS, and Ethylenediaminetetraacetic acid—EDTA 1:50 in DPBS—Thermo Fisher Scientific, Rockford, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Ιnterferon γ-induced protein (IP)-10 (also known as CXCL10) and tumor necrosis factor (TNF)-α gene expression in the cornea, conjunctiva, and lacrimal gland tissues was studied by quantitative real-time polymerase chain reaction with retrotranscription (qRT-PCR). All procedures were performed as previously described [ 55 ]. The corneas and conjunctivas of two eyes per mouse were pooled in the same Eppendorf tube, while for lacrimal glands one sample per mouse was used.…”
Section: Methodsmentioning
confidence: 99%
“… 295 Gehlsen et al found that lymphangiogenesis is involved in the pathogenesis of ocular GVHD. 296 In addition, Mertlitz et al found that acute GVHD was associated with lymphangiogenesis in murine allo-HSCT models and in intestinal tissue biopsy samples taken from patients, while the administration of anti-VEGFR3 antibodies suppressing lymphangiogenesis ameliorated GVHD and prolonged the survival in murine models. 297 …”
Section: Abnormal Lymphangiogenesis In Human Diseasesmentioning
confidence: 99%
“…It is not involved in corneal glucose uptake which is facilitated by glucose transporter-1 (GLUT1) [ 9 ]. Experimental studies, using mouse models of oGVHD [ 10 ] are under way to investigate insulin levels in tear film and its cellular effects in different phases and severities of oGVHD and to study the mode-of-action that we see in the first clinical applications.…”
Section: To the Editormentioning
confidence: 99%